Diagnosis and Evaluation of Railway Transport of Goods in Colombia - Pineda Jaramillo, Juan Diego (Ingeniería Solidaria, 2016)
Introduction: This article is the result of research carried out in the master’s thesis titled “Road and Railway transport mode choice model for general cargo to be xportedimported. Application to the Medellin-Port of Cartagena road system”, by Universidad Nacional de Colombia. The purpose of the research is to develop a diagnosis of the railway system in Colombia to discover the reasons why the Colombian industry, after mainly using the railway system to transport its goods for more than 100 years, is not using this mode of transport at present, to assess future possibilities to use this system for the transport of goods.Methodology: A qualitative research was conducted in this study to analyze the evolution of the railway from its creation to its decline and the current status of the Colombian railway system for the transport of goods. A focus group was then carried out to establish why the Colombian industry does not use the railway.Results: These reasons mainly include the lack of suitable infrastructure for the transfer of goods and the reliability of such mode of transport.Conclusions: The need to facilitate the implementation of a multimodal integration for freight transport in Colombia is huge; thus, the Colombian Government may influence the variables considered relevant for the industry to use the railway system when upgrading the railways.